The Legal Pluralism Strategy of Sendi Traditional Court in the Era of Modernization Law - Dicky Eko Prasetio; Fradhana Putra Disantara; Nadia Husna Azzahra; Dita Perwitasari (Rechtsidee, 2021)
The Sendi customary community is a community that has procedures for implementing customary law through the customary justice system. Not only that, the Sendi customary community also has a distinctive legal code and customary apparatus; so that its existence needs to be maintained in the face of the era of legal modernization. This research is an empirical legal research; by using secondary data types obtained from various searches for journal articles, books, and information through online news online; relating to the substance of the research. The purpose of this research is to describe the structure of Sendi's customary court in maintaining the existence of customary law; as well as describing the strategy of legal pluralism in Sendi's customary court to face modernization of law era. This empirical legal research focuses on the structure of Sendi's customary court with an approach of legal pluralism. The results of the study confirm that a legal pluralism strategy is needed to maintain the existence of the Sendi traditional court in the era of legal modernization; and integration efforts are needed between the law and the customary apparatus of Sendi with the law and the national or state apparatus.